2015
DOI: 10.1128/aem.00143-15
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcal 949 Group Phages Recognize a Carbohydrate Receptor on the Host Cell Surface

Abstract: Lactococcal bacteriophages represent one of the leading causes of dairy fermentation failure and product inconsistencies. A new member of the lactococcal 949 phage group, named WRP3, was isolated from cheese whey from a Sicilian factory in 2011. The genome sequence of this phage was determined, and it constitutes the largest lactococcal phage genome currently known, at 130,008 bp. Detailed bioinformatic analysis of the genomic region encoding the presumed initiator complex and baseplate of WRP3 has aided in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…The morphology of the Siphoviridae family has been well documented (group B as defined by Bradley [9]), and siphophages infecting L. lactis and S. thermophilus exhibit the expected morphology, with icosahedral heads and noncontractile tails. Phages infecting S. thermophilus in general possess longer tails than their lactococcal counterparts (with an exception being the 949 group of lactococcal phages [40,70]), their long tails being consistent with their long TMP-encoding genes (71). Upon electron microscopic analysis, it was found that phages 9871-4 exhibit icosahedral heads and relatively short tails (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The morphology of the Siphoviridae family has been well documented (group B as defined by Bradley [9]), and siphophages infecting L. lactis and S. thermophilus exhibit the expected morphology, with icosahedral heads and noncontractile tails. Phages infecting S. thermophilus in general possess longer tails than their lactococcal counterparts (with an exception being the 949 group of lactococcal phages [40,70]), their long tails being consistent with their long TMP-encoding genes (71). Upon electron microscopic analysis, it was found that phages 9871-4 exhibit icosahedral heads and relatively short tails (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Each of the 50 samples was tested against a panel of 25 L. lactis strains to isolate as wide a diversity of lactococcal phages as possible. The bacterial strains selected for this analysis were of known genotypes based on cell wall polysaccharide (CWPS) operon sequences from a previous study, as these are known to encode the receptor material for a variety of lactococcal phages [11,29]. Phage screening was performed using the standard double agar plaque assay as previously described [27] and a number of single plaque isolates from phage-containing samples were propagated on the relevant lactococcal host and plaque-purified at least twice to ensure homogeneity of the phage population.…”
Section: Methodsmentioning
confidence: 99%
“…DNA for sequencing of the selected phage genomes was extracted from 20 mL of fresh phage lysate (>10 8 pfu·mL −1 ) as described previously [11]. For genome sequencing, five µg of extracted DNA was used as verified by nanodrop quantification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations